Treatment interruption of biological drugs and tofacitinib in rheumatoid arthritis: A systematic review of case reports - Astrid Wiens; Helena Hiemisch Lobo Borba; Letícia Paula Leonart; Fernanda Stumpf Tonin; Laiza Maria Steimbach; Ariane Gonçalves Silva de Araújo; Thais Piazza; Vinicius Lins Ferreira; Roberto Pontarolo (Universidade de São Paulo, 2019)
The aim of this study was to evaluate interruption of treatment with biological drugs and tofacitinib due to adverse events in patients with rheumatoid arthritis. A systematic review was performed in the electronic databases MEDLINE, Cochrane, Scopus, CRD, IPA, Lilacs and Scielo. Case reports addressing interruption of treatment due to any adverse event related to abatacept (ABA), adalimumab (ADA), anakinra (ANA), certolizumab pegol (CER), etanercept (ETA), golimumab (GOL), infliximab (IFX), rituximab (RTX), secukinumab (SEC), tocilizumab (TCZ), tofacitinib (TOF) or ustekinumab (UST) in rheumatoid arthritis patients were evaluated. Baseline data, patient profile, previous and current treatments, cause of discontinuation and information on reintroduction of treatment were extracted from the case reports. One hundred and fifty-four studies (154 patients) reported 162 discontinuations of rheumatoid arthritis treatment due to adverse events (ETA = 57; IFX = 46; ADA = 32; TCZ = 13; RTX = 5; ANA = 3; GOL = 2; ABA = 2; TOF = 1; CER = 1; SEC = 0 and UST = 0). The mean age of patients was 56 (± 12.1) years and 82% were female. Seventy-four adverse events were confirmed (related to used drug), and 138 were observed in patients using anti-TNF. The most common adverse events were infections (21%), skin disease (15%), autoimmune disease (13%) and hematological disorders (9%). Case reports are important in the detection of rare adverse events and should be considered in the choice of appropriate therapy for patients.